At the crossroad - to be self-employ or entrepreneur. - Hulaimiah Mohd Nain, (2016)
Self-employ and entrepreneur is someone in different characteristics. Each of people in any category has their own ways and characteristics in manage their company. There are few differences if compare self-employ and entrepreneur. Based on the literature review, an entrepreneur, they will be defined when they more flexible, creative, confident, and passionate person. Meanwhile, for self-employed person they will be defined when very hard working, goal oriented, quality conscious and very good communicator. The interview was used as a research instruments in order to collect all the data from three respondents. Besides that, all the data have been analyzed via qualitative through manual analyzing data. Based on the case research findings, it can be concluded that self-employ and entrepreneur is different person. Based on the findings also, three respondents have similar characteristics and similar habit in the way they manage the company. Meanwhile, all the character found from the literature review is match with real characteristics of respondents. The three respondents have a few similar ways in manage their company. Other than that, all the characters are match with self-employ person in Malaysia.